Plant-Derived Exosome-like Nanoparticles from Emprit Ginger (Zingiber officinale var. Amarum) and Its Potential Metabolite as Functional Food Ingredients - Rukmi, Paramita Sadha Dayinta; Ratnadewi, Diah; Wijaya, Christofora Hanny (Bogor Agricultural University, Indonesia, 2026)
The Plant-Derived Exosome-like Nanoparticles (PDENs) are nano-sized vesicles secreted by plants that carry various bioactive compounds and have shown promise for use in functional food applications. This study investigated PDENs isolated from emprit ginger (Zingiber officinale var. Amarum), a local ginger variety renowned for its health-promoting properties. PDENs were extracted from rhizomes harvested at 8, 10, and 12 months, and analyzed for total phenolic content (TPC), total flavonoid content (TFC), and antioxidant capacity. The best-performing sample based on these parameters was selected for further metabolite profiling using LC-QTOF-MS. A total of 41 compounds were identified from the selected GDEN and ginger extract samples—32 compounds in the GDEN and 24 in the extract. These compounds belong to various groups, including amino acids, flavonoids, phenolics, lipids, terpenoids, vitamins, and others. Compound identification was based on public databases and literature concerning their potential as functional food ingredients. Among these, amino acids were the most abundant group in the GDENs, whereas phenolics were the dominant group in the ginger extract. This study underscores the potential of ginger-derived exosome nanoparticles as a rich source of bioactive compounds, supporting their further exploration and application in the development of functional food products. The balanced metabolite profile observed in GDENs highlights their unique advantages over conventional extracts. These findings reinforce the potential of emprit GDENs as promising candidates for functional food development.